Functional Mapping of Adhesiveness on Live Cells Reveals How Guidance Phenotypes Can Emerge From Complex Spatiotemporal Integrin Regulation - Robert, Philippe; Biarnes-Pelicot, Martine; Garcia-Seyda, Nicolas; Hatoum, Petra; Touchard, Dominique; Brustlein, Sophie; Nicolas, Philippe; Malissen, Bernard; Valignat, Marie-Pierre; Theodoly, Olivier (Frontiers in Bioengineering and Biotechnology, 2021)
Immune cells have the ubiquitous capability to migrate disregarding the adhesion properties of the environment, which requires a versatile adaptation of their adhesiveness mediated by integrins, a family of specialized adhesion proteins. Each subtype of integrins has several ligands and several affinity states controlled by internal and external stimuli. However, probing cell adhesion properties on live cells without perturbing cell motility is highly challenging, especially in vivo. Here, we developed a novel in vitro method using micron-size beads pulled by flow to functionally probe the local surface adhesiveness of live and motile cells. This method allowed a functional mapping of the adhesiveness mediated by VLA-4 and LFA-1 integrins on the trailing and leading edges of live human T lymphocytes. We show that cell polarization processes enhance integrin-mediated adhesiveness toward cell rear for VLA-4 and cell front for LFA-1. Furthermore, an inhibiting crosstalk of LFA-1 toward VLA-4 and an activating crosstalk of VLA-4 toward LFA-1 were found to modulate cell adhesiveness with a long-distance effect across the cell. These combined signaling processes directly support the bistable model that explains the emergence of the versatile guidance of lymphocyte under flow. Molecularly, Sharpin, an LFA-1 inhibitor in lymphocyte uropod, was found involved in the LFA-1 deadhesion of lymphocytes; however, both Sharpin and Myosin inhibition had a rather modest impact on adhesiveness. Quantitative 3D immunostaining identified high-affinity LFA-1 and VLA-4 densities at around 50 and 100 molecules/μm2 in basal adherent zones, respectively. Interestingly, a latent adhesiveness of dorsal zones was not grasped by immunostaining but assessed by direct functional assays with beads. The combination of live functional assays, molecular imaging, and genome editing is instrumental to characterizing the spatiotemporal regulation of integrin-mediated adhesiveness at molecular and cell scales, which opens a new perspective to decipher sophisticated phenotypes of motility and guidance.